Outcomes of an Emergency Department opioid alternatives Program implemented within a safety-net hospital system - Magda Montague; Charlotte Hopson; Claire Layton; Jennifer Fishe; Ashley Norse; L. Kendall Webb; Petra Duran-Gehring; Andrew Bertrand; Jennifer Brailsford; Taylor Munson; Rui Wang; Nolan Menze; et al. (BMC Emergency Medicine)
Abstract Background The ongoing opioid epidemic in the United States has reinforced the need to provide multimodal and non-opioid pain management interventions. The PAMI-ED ALT program employed a multifaceted approach in the Emergency Department (ED) developing electronic health record (EHR) pain management order panels and discharge panels, as well as educating patients, clinicians, and ED staff on opioid alternatives, including non-pharmacologic interventions. The primary objective of this analysis was to compare changes in opioid and non-opioid analgesic administrations and prescribing in ED patients with select pain conditions (renal colic, headache, low back, and non-low back musculoskeletal pain) before and after implementation of PAMI ED-ALT. Secondary outcomes included characterizing changes in 30-day ED all-cause recidivism and hospital all-cause admissions within these pain populations. Methods Demographics, opioid and opioid alternative utilization, hospital admission, 30-day ED returns and change in pain intensity score were collected from January 2019-March 2020 (pre-program implementation) and January 2021-March 2023 (post-program implementation) for both the ED aggregate and program target pain populations. Results Pain management order panel utilization increased throughout the post-implementation period. When comparing pre to post program data, there was a reduction in opioid administrations and prescriptions for most of the target pain conditions, as well as within the ED aggregate population. Opioid alternative administrations and prescriptions increased for all pain conditions except renal colic. Hospital admissions decreased significantly amongst those with low back pain and headache/migraine and 30-day ED returns significantly declined in those with musculoskeletal pain. Conclusion Our findings demonstrate an opioid-alternatives program implemented within a safety-net hospital system serving a predominantly socially disadvantaged patient population can lead to changes in ED pain management and potentially reduce 30-day ED recidivism and hospitalizations.